A method for reusing a spent hydroprocessing catalyst
Patent Information
- Application Number
- CN202310237411.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-14
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-03-14
AI Technical Summary
The recovery process of waste hydrotreating catalysts in existing technologies is complex, energy-intensive, and prone to generating toxic and harmful gases. Furthermore, it is highly destructive to the alumina support, resulting in insufficient utilization of metal components.
Low-temperature oxidation treatment is used to partially oxidize the waste hydrotreating catalyst, followed by leaching with phosphate or organic acid ions solution, and the preparation of a new support by combining pseudoboehmite, thus avoiding high-temperature roasting and the use of strong oxidants.
This method enables simple and low-energy recovery of waste hydrogenation catalysts, reduces toxic gas emissions, improves the utilization efficiency of metals and supports, and reduces the risk of alumina leaching from the support.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of catalyst separation and recovery technology, and relates to a method for reusing waste hydrotreating catalysts, specifically a method for recycling and reusing waste hydrotreating catalysts. Background Technology
[0002] Currently, the world generates 700,000 to 900,000 tons of spent catalysts annually due to production in the petroleum and chemical industries, and this amount is continuously increasing. Hydrotreating catalysts used in oil refining contain approximately 20-30 wt% of metals, such as molybdenum and nickel. Recycling these catalysts not only solves the problem of solid hazardous waste disposal but also increases economic benefits and alleviates the shortage of metal mineral resources. When discharging spent catalysts, plants typically first flush the catalyst bed with light oil, followed by high-temperature stripping. The discharged catalyst contains a small amount of light oil components.
[0003] Industrial hydrogenation catalysts mainly exist in the form of sulfide. Because the valence band of MoS2 comes only from the metal orbitals, and the valence band does not contribute to the chemical bond between the metal and sulfur in the crystal, MoS2 can only be degraded by oxidation attack, not by proton attack. Therefore, MoS2 has good chemical and thermal stability, is insoluble in water and dilute acid, and can be corroded by concentrated sulfuric acid, concentrated nitric acid, boiling concentrated hydrochloric acid, aqua regia, pure oxygen, fluorine and chlorine (Zhang Heng, Properties, Production and Application of Molybdenum Disulfide [J]. China Molybdenum Industry, 2014, 38(1):7-10). At present, the main recycling processes for waste hydrogenation catalysts are: roasting-sodium carbonate leaching, acid-base two-step leaching, sodium carbonate roasting-water leaching, pyrometallurgical enrichment-wet separation combined process, etc. Roasting is usually required to convert the sulfide metal into the oxidized state. This process is not only energy-intensive, but also produces toxic and harmful gases such as sulfur dioxide and carbon dioxide. At the same time, the use of substances containing Na makes subsequent washing and impurity removal difficult. In primary molybdenite, molybdenum exists as molybdenum sulfide. During the pressurized oxidative leaching process, molybdenum in molybdenite can be converted into soluble molybdates and enter the solution: MoS₂ + 6OH⁻ - +4.5O2=MoO4 2- +2SO4 2-Under suitable conditions, the leaching rate of molybdenum can reach over 95 wt% (Peng Jianrong et al., Study on pressure alkaline leaching of primary molybdenum ore, Rare Metals, 2007, 31: 110-113). Similarly, SP Barik et al. (Barik SP, et al. Direct leaching of molybdenum and cobalt from spent hydrodesulphurization catalyst with sulfuric acid[J]. Hydrometallurgy, 2012, 111: 46-51.) used hydrogen peroxide as an oxidant and leached it together with sulfuric acid to remove spent hydrodesulfurization catalyst that had only been washed and dried with water. Under suitable conditions, over 90% of Mo and Co could be recovered. Patent CN 113564386 A first uses acetone to remove oil from the spent nickel-molybdenum catalyst, then mixes hydrogen peroxide with the spent nickel-molybdenum catalyst and reacts it further with ammonia to obtain an ammonia-containing filtrate. Acid is then added for acidification and precipitation to obtain ammonium molybdate. This method uses a large amount of hydrogen peroxide, which increases the recovery cost. Furthermore, the high dissolution rate of the carrier alumina puts significant pressure on subsequent metal separation and purification.
[0004] US4888316 discloses a method for utilizing spent catalyst containing coke, which includes grinding the coke-containing waste catalyst, mixing it with an alumina-containing material, molding it, and heating the molded mixture to burn off the coke remaining in the waste catalyst. This patent utilizes the coke on the spent catalyst as a pore-expanding agent, with the coke volatilizing during the support roasting stage. However, this method results in the underutilization of the metal components of the spent catalyst, and the alumina support is not surface-modified, leading to poor colloidal properties and low strength in the newly prepared support.
[0005] CN 105709853 B discloses a method for recycling waste hydrotreating catalysts. The waste hydrotreating catalyst is deoiled, ground into powder, and washed with hydrochloric acid to remove calcium and iron deposits. Chlorine and air are then introduced to react, yielding chlorides or chlorine oxides of metallic molybdenum, nickel, cobalt, or vanadium. The catalyst is then volatilized, and the gas and solid phases are separated. The metal is recovered by condensation from the gas phase. The remaining solid residue is washed with water or an acidic solution, dried, and mixed with an extrusion aid and binder to form a composite material. The mixture is then calcined in a nitrogen atmosphere to prepare an alumina-carbon composite support. This process uses highly toxic chlorine gas, posing significant operational risks.
[0006] In summary, in the existing technology, the waste hydrotreating catalyst first needs to be roasted at high temperature or an oxidant is used to convert all the active metal into oxidized metal before leaching. This process is complicated, easily generates toxic and harmful gases (such as carbon dioxide and hydrogen sulfide), and is highly destructive to the alumina support. Summary of the Invention
[0007] To overcome the shortcomings of existing technologies, this invention provides a method for reusing waste hydrotreating catalysts. Using this method, the waste hydrotreating catalyst requires only a simple, shallow oxidation treatment, resulting in partial oxidation of metal sulfides. Most of the molybdenum and nickel are leached in the form of sulfur oxides, and the molybdenum and nickel in the leachate exist as sulfur-containing complexes. After concentration, the leachate can be used to impregnate a support. The remaining carbonaceous support, after leaching treatment, exhibits significantly improved surface properties and can be used to prepare new supports.
[0008] A method for reusing spent hydrotreating catalyst, the method comprising the following steps: firstly, the spent hydrotreating catalyst is oxidized to reduce the sulfur content in the treated spent hydrotreating catalyst by 10-65 wt%, preferably by 20-60 wt%, and more preferably by 25-50 wt%; then, the treated material is leached; finally, the leaching solution and solid material are obtained by separation.
[0009] In the method of the present invention, the oxidation treatment can be a conventional oxidation treatment method in the prior art, and the oxidant used can be one or more of oxygen, air, humid air, oxygen-containing gas mixture, hydrogen peroxide, and sodium chlorate, preferably air or oxygen-containing gas mixture.
[0010] In the method of the present invention, the oxidation treatment is a low-temperature heat treatment in an oxygen-containing atmosphere, wherein the treatment temperature is 120-400℃, preferably 150-350℃, and more preferably 200-280℃; and the treatment time is 0.5-10h, preferably 1-8h, and more preferably 2-5h.
[0011] In the method of the present invention, the sulfur content in the waste hydrogenation catalyst before treatment is 4-16 wt%, preferably 6-13 wt%, and the sulfur content is based on the mass of elemental sulfur and the weight of the waste hydrogenation catalyst.
[0012] In the method of the present invention, the waste hydrogenation catalyst before or after treatment uses alumina as a support and Group VIB and Group VIII metals as active components, wherein the Group VIB metal is at least molybdenum and the Group VIII metal is cobalt and / or nickel.
[0013] In the method of the present invention, based on the weight of the waste hydrogenation catalyst before treatment, the molybdenum content, calculated as molybdenum oxide, is 5-40 wt%, preferably 15-25 wt%; and the nickel content, calculated as nickel oxide, is 2-10 wt%, preferably 3-7 wt%.
[0014] This invention discloses a method for reusing waste hydrotreating catalysts, specifically comprising the following steps: (1) Waste hydrotreating catalyst is oxidized and then ground into powder; (2) Use acidic and / or alkaline solutions as leaching solutions to leach the waste hydrogenation catalyst powder ground into powder in step (1); (3) Filter the material after leaching in step (2) to obtain leaching solution and solid material; Optionally, (4) the solid material obtained in step (3) is mixed, shaped, dried and calcined to obtain a carrier; Further optionally, (5) the leaching solution obtained in step (3) is impregnated onto the molded support, preferably the support obtained in step (4), to prepare a new hydrogenation catalyst.
[0015] Furthermore, the waste hydrotreating catalyst mentioned in step (1) is the hydrotreating catalyst after being stripped out by gas, and the waste hydrotreating catalyst cannot be regenerated. If the gas stripping time is long or the temperature is high before unloading, the pretreatment temperature can be appropriately reduced; at the same time, if the oxidation treatment temperature is high, the treatment time can be appropriately shortened.
[0016] Furthermore, the oxidation treatment in step (1) is a thermal treatment of the waste hydrotreating catalyst in a flowing, oxygen-containing atmosphere (preferably air).
[0017] Furthermore, the acidic or alkaline solution in step (2) contains at least one of phosphate and organic acid radicals. The phosphate-containing substances include, but are not limited to, one or more of phosphoric acid, ammonium phosphate, diammonium hydrogen phosphate, diammonium dihydrogen phosphate, and hydroxyphosphate; the organic acid-containing substances include, but are not limited to, one or more of oxalic acid, citric acid, tartaric acid, malic acid, ascorbic acid, ammonium oxalate, and ammonium citrate.
[0018] Furthermore, in step (2), the concentration of phosphate in the acidic or alkaline solution is 0.05-1 mol / L, preferably 0.2-0.6 mol / L; and the concentration of organic acid anions is 0.01-1 mol / L, preferably 0.4-0.6 mol / L.
[0019] Furthermore, in step (2), the ratio of the amount (mass) of the waste hydrotreating catalyst to the volume of the leaching solution is 1 g / (3-20) ml, preferably 1 g / (5-10) ml; the leaching temperature is 60-120℃, preferably 90-110℃; and the leaching time is 30-150 min, preferably 60-120 min.
[0020] Furthermore, in step (2), the number of extractions is 1-6 times, preferably 2-4 times, and the extraction solution and operating conditions used each time can be the same or different.
[0021] Furthermore, the separation in step (3) is carried out by filtration. The filtration can be carried out at an appropriate temperature, for example, at an immersion temperature of 80-120°C, preferably 90-110°C.
[0022] Furthermore, the leaching solution obtained in step (3) can be used directly or after concentration as an active metal impregnation solution; for example, evaporation or membrane filtration can be used. A certain amount of active metal can also be added to the impregnation solution to increase the concentration; additional agents can also be added according to the modification needs to improve the performance of the impregnation solution.
[0023] Furthermore, the solid material obtained in step (3) has a carbon content (based on elemental composition) of 2-23 wt% (in the dried state) based on its total mass, preferably 4-10 wt%.
[0024] Furthermore, in step (3), the obtained solid material or an appropriate amount of boehmite is added and kneaded to prepare an alumina carrier. The proportion of boehmite added is 20-90 wt% of the alumina carrier, preferably 40-60 wt%.
[0025] Due to the high chemical and thermal stability of MoS2 in spent hydrotreating catalysts, existing technologies generally employ high-temperature calcination under an oxygen-containing atmosphere or oxidation with strong oxidants to completely oxidize the active metals, including MoS2, before leaching and reuse. This invention, through in-depth research, has discovered that after partial oxidation treatment (oxidizing the sulfide metals in the spent hydrotreating catalyst), under suitable temperature and in a leaching solution containing phosphate and organic acid radicals, active metals, including Mo, can be dissolved. The resulting filter residue contains alumina with a certain amount of coke, which can be used to prepare macroporous alumina supports.
[0026] Further analysis revealed that although pure MoS2 is difficult to leach, the hydrotreating catalyst also contains a certain proportion of Ni and / or Co. Ni and / or Co from the spent hydrotreating catalyst may enter the MoS2 lattice, increasing its solubility. Simultaneously, partial oxidation treatment causes partial oxidation of the metal sulfides, disrupting the original sulfide structure and leading to lattice distortion and defects. The strong complexing effect of phosphate and organic acid ions allows for the leaching of most of the active metals, including molybdenum, from the spent catalyst without the need for high-temperature roasting or complete oxidation with oxidants such as hydrogen peroxide.
[0027] Compared with existing technologies, this invention eliminates the need for deep treatment of spent catalysts, reducing energy consumption and hydrogen sulfide emissions during the process. The use of weak acids or ammonium salts of weak acids during leaching reduces the risk of alumina leaching and equipment corrosion. Compared to conventional methods, the process is simpler and more environmentally friendly. It also enables the recycling of both the metal and the support. Implementation
[0028] The following examples and comparative examples further illustrate the preparation effect of the present invention. It should be understood that the specific embodiments described are only for illustrating and explaining the present invention and are not intended to limit the present invention. In the context of the present invention, unless otherwise specified, % refers to mass percentage.
[0029] In the following examples or comparative examples, the spent hydrotreating catalyst came from a hydrocracking pretreatment unit of an oil refinery. The contents of Mo and Ni were determined by inorganic colorimetry, following the standards Q / SHFRIPP 0400012-2005 and Q / SHFRIPP 0400046-2005, respectively. The sulfur and carbon contents of the spent catalyst were obtained by chromatography, following the standards Q / SHFRIPP040053-2009 and Q / SHFRIPP040053-2009-200X, respectively. Phase information was obtained by X-ray diffraction (XRD). Surface and pore structure information was obtained by low-temperature nitrogen adsorption-desorption. The composition and chemical state analysis of the solid sample surface were obtained by X-ray photoelectron spectroscopy (XPS). The impurity ion content in the impregnation solution was determined using inductively coupled plasma atomic emission spectrometry (ICP). When evaluating the catalyst performance, a sulfidation operation was first performed, and then the hydrodesulfurization and hydronitrogenation performance of conventional diesel fuel was investigated under the conditions of 340℃, 6MPa, space velocity 2.0h-1, and hydrogen-to-oil ratio of 500.
[0030] Example 1 (1) Waste hydrotreating catalyst (properties shown in Table 1) was ground into powder after oxidation treatment; the oxidation treatment was carried out in air atmosphere at low temperature of 200°C for 3 hours, and the mass content of sulfur element was reduced by 25%; (2) An acidic solution was used as the leaching solution to leach the waste hydrogenation catalyst powder ground into powder in step (1). The composition of the leaching solution was as follows: a mixed solution of phosphoric acid and citric acid, wherein the concentrations of phosphate and citrate were 0.3 mol / L and 0.5 mol / L, respectively; the volume ratio of waste hydrogenation catalyst to leaching solution was 1 g / 6 ml; the leaching temperature was 100 °C; the leaching time was 60 min; and the number of leaching times was 2. After the first leaching, the filter was filtered, and the filter residue was leached again. The operating conditions were the same for both leaching times, and the filtrates obtained from the two leaching times were mixed. (3) The calculated extraction rates of Mo and Ni and the content of Al in the leachate are shown in Table 2; (4) The solid material obtained in step (3) is mixed, shaped, dried and calcined after adding pseudoboehmite to obtain a carrier (denoted as ZT-A). The properties of the carrier are shown in Table 3. The amount of pseudoboehmite added is 40 wt% of the mass of the solid material. (5) After evaporating 80% of the water from the leachate obtained in step (3), the Mo and Ni contents are determined. Metals are added according to the metal content of the industrial reference leachate. After heating and dissolving, the solution is filtered to obtain a new leachate. The carrier obtained in step (4) is used to prepare a new hydrotreating catalyst, denoted as CAT-1. The composition and properties of the catalyst are shown in Table 4, and the properties and evaluation results of the oil are shown in Table 5.
[0031] Example 2 The waste hydrotreating catalyst (same as in Example 1, properties shown in Table 1) was ground into powder after oxidation treatment. The oxidation treatment was a low-temperature heat treatment in air atmosphere at a temperature of 250°C for 2 hours, resulting in a 43% reduction in the mass content of sulfur. The remaining conditions were the same as in Example 1. The resulting support was designated ZT-B, and the catalyst was designated CAT-2.
[0032] Example 3 The waste hydrotreating catalyst (same as in Example 1, properties shown in Table 1) was oxidized and then ground into powder. The oxidation treatment was a low-temperature heat treatment in air atmosphere at a temperature of 280°C for 2 hours, which reduced the sulfur content by 50%. The remaining conditions were the same as in Example 1. The resulting support was designated ZT-C, and the catalyst was designated CAT-3.
[0033] Example 4 The waste hydrotreating catalyst (same as in Example 1, properties shown in Table 1) was oxidized and then ground into powder. The oxidation treatment was a low-temperature heat treatment in an air atmosphere at a temperature of 280°C for 2 hours. An acidic solution was used as the leaching liquid to leach the waste hydrotreating catalyst powder ground in step (1). The leaching liquid consisted of 0.3 mol / L phosphoric acid. Other conditions were the same as in Example 1. The resulting support was designated ZT-D, and the catalyst was designated CAT-4.
[0034] Example 5 The waste hydrotreating catalyst (same as in Example 1, properties shown in Table 1) was oxidized and then ground into powder. The oxidation treatment was a low-temperature heat treatment in an air atmosphere at a temperature of 280°C for 2 hours. A weakly alkaline solution was used as the leaching liquid to leach the waste hydrotreating catalyst powder ground in step (1). The leaching liquid consisted of 0.3 mol / L ammonium phosphate. The remaining conditions were the same as in Example 1. The resulting support was designated ZT-E, and the catalyst was designated CAT-5.
[0035] Example 6 The waste hydrotreating catalyst (same as in Example 1, properties shown in Table 1) was oxidized and then ground into powder. The oxidation treatment was a low-temperature heat treatment in an air atmosphere at a temperature of 280°C for 2 hours. An acidic solution was used as the leaching liquid to leach the waste hydrotreating catalyst powder ground in step (1). The leaching liquid consisted of 0.3 mol / L ammonium oxalate. Other conditions were the same as in Example 1. The resulting support was designated ZT-F, and the catalyst was designated CAT-6.
[0036] Example 7 Except for the use of 60 wt% boehmite in the preparation of the new support, all other conditions were the same as in Example 2. The resulting support was designated ZT-G, and the catalyst was designated CAT-7.
[0037] Comparative Example 1 The waste hydrotreating catalyst (same as in Example 1, properties are shown in Table 1) was ground into powder after oxidation treatment. The oxidation treatment was carried out in an air atmosphere at a high temperature of 500°C for 3 hours. The mass content of sulfur was reduced by 96%. The remaining treatment conditions were the same as in Example 3.
[0038] Comparative Example 2 The waste hydrotreating catalyst (same as in Example 1, properties are shown in Table 1) was deoiled by solvent and then ground into powder. After drying at 100°C for 5 hours, a leaching experiment was conducted under the same conditions as in Example 1.
[0039] Table 1. Properties of catalysts from waste hydrocracking pretreatment
[0040] Table 2. Metal leaching rate and Al content in filtrate
[0041] *Mo and Ni leaching rates were calculated by measuring the content in the solid before and after leaching using an inorganic colorimetric method and then comparing the results. Al content was obtained using ICP; when the concentration was high, it was measured after dilution.
[0042] Table 3. Properties of the newly prepared carrier
[0043] *The filter residue was dried at 120℃ and then mixed with boehmite and additives. After kneading, molding, and drying, it was calcined at 600℃ for 3 hours and other properties were then determined.
[0044] Table 4. Properties of the newly prepared catalysts
[0045] *The reference catalyst is a catalyst prepared using an industrial alumina support and impregnation solution, with a metal content comparable to that of the examples.
[0046] Table 5. Catalytic performance of catalysts
[0047] *Catalyst performance evaluation conditions: For catalyst performance evaluation, a sulfidation process was first performed using DMDS-containing sulfurized oil, followed by evaluation at 340℃, 6MPa, and a space velocity of 2.0h. -1 The hydrodesulfurization and hydronitrogenation performance of conventional three-line diesel was investigated under a hydrogen-to-oil ratio of 500.
Claims
1. A method for reusing waste hydrotreating catalyst, characterized in that: The method includes the following steps: First, the waste hydrogenation catalyst is oxidized to reduce the sulfur content in the treated waste hydrogenation catalyst by 10-65 wt% compared to the sulfur content in the untreated waste hydrogenation catalyst; then, the treated material is leached; finally, the leaching solution and solid material are separated. Solid materials are mixed, shaped, dried, and calcined to obtain a molded carrier; The leaching solution is used to impregnate the molded support to obtain the hydrogenation-treated catalyst; The oxidation treatment is a low-temperature heat treatment performed in an oxygen-containing atmosphere, with a treatment temperature of 200-280℃ and a treatment time of 2-5 hours. The waste hydrotreating catalyst is the hydrotreating catalyst that has been stripped out by gas, and the waste hydrotreating catalyst cannot be regenerated. The leaching process uses acidic and / or alkaline solutions as leaching solutions; the acidic and / or alkaline solutions contain at least one of phosphate ions and organic acid ions; The sulfur content in the waste hydrogenation catalyst before treatment is 4-16 wt%, and the sulfur content is based on the mass of elemental sulfur and the weight of the waste hydrogenation catalyst. The waste hydrogenation catalyst before or after treatment uses alumina as a support and Group VIB and Group VIII metals as active components, wherein the Group VIB metal is at least molybdenum and the Group VIII metal is cobalt and / or nickel. The concentration of phosphate in acidic or alkaline solutions is 0.05-1 mol / L; the concentration of organic acid anions is 0.01-1 mol / L. The mass ratio of the waste hydrotreating catalyst to the volume of the leaching solution is 1 g / (3-20) ml; the leaching temperature is 60-120℃; and the leaching time is 30-150 min.
2. The method according to claim 1, characterized in that, The sulfur content in the treated waste hydrogenation catalyst is reduced by 20wt%-60wt% compared to the sulfur content in the untreated waste hydrogenation catalyst.
3. The method according to claim 1, characterized in that, The sulfur content in the treated waste hydrogenation catalyst is reduced by 25wt%-50wt% compared to the sulfur content in the untreated waste hydrogenation catalyst.
4. The method according to claim 1, characterized in that: The oxidation treatment is a conventional oxidation treatment method in the prior art, and the oxidant used is one or more of oxygen, air, humid air, oxygen-containing gas mixtures, hydrogen peroxide, and sodium chlorate.
5. The method according to claim 4, characterized in that: The oxidant used is air or a mixture of oxygen-containing gases.
6. The method according to claim 1, characterized in that: The sulfur content in the waste hydrogenation catalyst before treatment is 6-13 wt%, and the sulfur content is based on the mass of elemental sulfur and the weight of the waste hydrogenation catalyst.
7. The method according to claim 1, characterized in that: Based on the weight of the waste hydrogenation catalyst before treatment, the molybdenum content (calculated as molybdenum oxide) is 5-40 wt%; the nickel content (calculated as nickel oxide) is 2-10 wt%.
8. The method according to claim 7, characterized in that: Based on the weight of the waste hydrogenation catalyst before treatment, the molybdenum content (calculated as molybdenum oxide) is 15-25 wt%; the nickel content (calculated as nickel oxide) is 3-7 wt%.
9. The method according to claim 1, characterized in that: Specifically, the following steps are included: (1) Waste hydrotreating catalyst is oxidized and then ground into powder; (2) Use acidic and / or alkaline solutions as leaching solutions to leach the waste hydrogenation catalyst powder ground into powder in step (1); (3) Filter the material after leaching in step (2) to obtain leaching solution and solid material; (4) The solid material obtained in step (3) is mixed, shaped, dried and calcined to obtain a carrier; (5) The leaching solution obtained in step (3) is used to impregnate the molded carrier and the carrier obtained in step (4) to prepare a new hydrogenation catalyst.
10. The method according to claim 9, characterized in that: The oxidation treatment in step (1) is a thermal treatment of the waste hydrotreating catalyst in a flowing, oxygen-containing atmosphere.
11. The method according to claim 10, characterized in that: The oxidation treatment in step (1) is to heat-treat the waste hydrotreating catalyst in air.
12. The method according to claim 9, characterized in that: The acidic or alkaline solution in step (2) contains at least one of phosphate and organic acid ions; the substance containing the phosphate ion includes one or more of phosphoric acid, ammonium phosphate, phosphoric acid, diammonium hydrogen phosphate, diammonium dihydrogen phosphate, and hydroxyphosphoric acid; the substance containing the organic acid ion includes one or more of oxalic acid, citric acid, tartaric acid, malic acid, ascorbic acid, ammonium oxalate, and ammonium citrate.
13. The method according to claim 9, characterized in that: In step (2), the concentration of phosphate in the acidic or alkaline solution is 0.05-1 mol / L; the concentration of organic acid is 0.01-1 mol / L.
14. The method according to claim 9, characterized in that: In step (2), the concentration of phosphate in the acidic or alkaline solution is 0.2-0.6 mol / L; the concentration of organic acid is 0.4-0.6 mol / L.
15. The method according to claim 9, characterized in that: In step (2), the mass ratio of the waste hydrotreating catalyst to the volume of the leaching solution is 1 g / (3-20) ml; the leaching temperature is 60-120℃; and the leaching time is 30-150 min.
16. The method according to claim 15, characterized in that: In step (2), the mass ratio of the waste hydrotreating catalyst to the volume of the leaching solution is 1 g / (5-10) ml; the leaching temperature is 90-110℃; and the leaching time is 60-120 min.
17. The method according to claim 9, characterized in that: In step (2), the extraction is performed 1-6 times, and the extraction solution and operating conditions used each time are the same or different.
18. The method according to claim 17, characterized in that: In step (2), the soaking is performed 2-4 times.
19. The method according to claim 9, characterized in that: In step (3), the separation is carried out by filtration at a temperature of 80-120℃.
20. The method according to claim 19, characterized in that: In step (3), the separation is carried out by filtration at a temperature of 90-110℃.
21. The method according to claim 9, characterized in that: In step (3), the obtained leaching solution is used directly or after concentration as an active metal leaching solution.
22. The method according to claim 9, characterized in that: The carbon content of the solid material obtained in step (3) is 2-23 wt% based on its total mass.
23. The method according to claim 22, characterized in that: The solid material obtained in step (3) has a carbon content of 4-10 wt% based on its total mass.
24. The method according to claim 9, characterized in that: In step (3), the obtained solid material or an appropriate amount of boehmite is added and kneaded to prepare an alumina carrier. The proportion of boehmite added is 20-90 wt% of the alumina carrier.
25. The method according to claim 24, characterized in that: In step (3), the obtained solid material or an appropriate amount of boehmite is added and kneaded to prepare an alumina carrier. The proportion of boehmite added is 40-60 wt% of the alumina carrier.
Citation Information
Patent Citations
A method for recycling waste hydrogenation catalyst
CN105709853B
Method for recovering molybdenum from waste nickel-molybdenum catalyst
CN113564386A
Preparation of hydrotreating catalyst from spent catalyst
US4888316A
Hydrogenation catalyst regenerating method
CN109926105A
Preparation method of hydrogenation carbon residue removal catalyst
CN114602484A
